Editors' Introduction - Michael Glanzberg; Barbara H Partee; Jurģis Šķilters (Baltic International Yearbook of Cognition, Logic and Communication, 2010)
The papers published in this volume were presented at the 6th International Symposium of Cognition, Logic and Communication, entitled ‘Formal Semantics and Pragmatics: Discourse, Context, and Models’, taking place at the University of Latvia, Riga, initially scheduled for April 2010.